Faktor-Faktor eksogen yang Berhubungan dengan Kejadian Dermatitis Kontak Akibat Kerja(DKAK) pada Pekerja Batik di Jambi - Desi Primayani (PHARMANAJA : PHARMACEUTICAL JOURNAL OF UNAJA, 2025)
Occupational Contact Dermatitis (OCD) is among the most prevalent occupational skin diseases, particularly affecting informal sector workers such as batik artisans who are chronically exposed to chemical substances. This study aimed to identify exogenous factors associated with the incidence of OCD among batik workers in Jambi. A quantitative approach with a cross-sectional design was applied, involving a number of respondents from several batik production centers in Jambi. Data were collected using structured questionnaires and analyzed using chi-square tests and logistic regression to examine the associations between exogenous variables—including duration of exposure, type of chemicals, use of personal protective equipment (PPE), and frequency of contact—and the occurrence of OCD. The results revealed significant associations between inconsistent use of PPE, chemical exposure duration exceeding five years, and high contact frequency with OCD incidence (p < 0.05). These findings underscore the need for preventive interventions through enhanced PPE utilization and education on chemical hazards among batik workers. This study contributes to the development of more adaptive occupational health strategies in home-based industries.